VITRINITE REFLECTANCE STUDIES OF DISPERSED ORGANIC MATERIAL FROM NORTHLAND ALLOCHTHON ROCKS, NORTH ISLAND, NEW ZEALAND - Aadil, N.; D. Sohail, G. M. (The Nucleus, 2014)
The Northland Allochthon is a structurally displaced rock unit locat ed between Three Kings Island and Mt. Camel in northern North Island, New Zealand. Lithologically, the allochthonous unit is composed of different lithofacies comprising sandstone, siltst one, greensand, siliceous mudstone, argillaceous micritic limestone and rare coal measures alongwith dispersed organic matter. In this paper, vitrinite reflectance of dispersed organic matter in non-coaly clastic rocks from different lithofacies of Northland Allochthon, Rocks, North Island, New Zealand is analyzed to assess the degree of diagenesis of organic matter and paleo temperature. Vitrinite Reflectance values range from 0.30 to 2.00 %Rm and correspond to estimate of palaeotemperature of 60 to 180 C. Oldest sedimentary complex may have been affected by heating to 300 C from intrusion of keratophyre dykes.